Students’ Perception of Total Physical Response Method in Teaching English Vocabulary at Ban Nonsawan School, Thailand - Putri Amara Dzurotul Ilmi; Khoirul Anwar (Journal of Languages and Language Teaching, 2022)
When the teacher teach vocabulary about body parts in class, they use rhythm and movement to make students understand each body name. That is called the Total Physical Response (TPR) method. This study aims to investigate the student’s perception on Total Physical Response (TPR) method as a technique in teaching English vocabulary. The research study used a qualitative descriptive method. To achieve the research objectives, the data was taken from two sources: questionnaire and interview in eighth graders at a Secondary School in Loei, Thailand, namely Ban Nonsawan School. An overall, 30 students were involved in the study. The results obtained reveal that Total Physical Response technique allows students to study harder and easier in learning English vocabulary. In addition, the result showed some improvement on get a new vocabulary with this technique. Moreover, the data showed that there were some benefits of Total Physical Response method: 1. Develop students’ speaking abilities and vocabulary mastery, 2. Increase student participation in class, 3. Having a fun learning atmosphere.